Restoration of Stocking and Biodiversity in Western Ghats - Singh, U. V. (Indian Forester, 1995)
Western Ghats of Deccan plateau are highly biodiversified among the ecosystems available on earth. Because of faulty management practices and increased biotic pressures the area is losing its character at a faster rate. To check and restoration, different strategies are being adopted for different types of areas. Areas of mono culture plantation, degraded forests, low crown density wood lots are being treated and planted with different endemic and exotic species.